The impact of draught on work performance in spaces with ceiling heating - András-Tövissi, Balázs; Kajtár, László; Nyers, József (Journal of Production Engineering, 2020)
Due to the proliferation of different ceiling heating technologies, an increasing number of individuals find themselves working long hours in rooms equipped with ceiling heating and mechanical ventilation systems. Achieving optimal thermal comfort is crucial for enhancing the efficiency of employees’ work in such environments. In this context, it becomes highly significant to understand the combined impact of radiation temperature asymmetry, resulting from the warm ceiling, and the presence of draughts. Research in the existing literature concerning the combined effects of these two localized discomfort factors remains incomplete. In the current study, an experiment involving 20 participants, comprising 10 women and 10 men, was conducted to investigate how draughts affect work performance in spaces with ceiling heating. The primary outcome of this research aims to determine how draughts influence the speed and accuracy of work in such settings.